ANALISIS KEPUASAN PELANGGAN AGEN PERJALANAN ONLINE (OTA) APLIKASI MOBILE DI YOGYAKARTA: PENDEKATAN KUANTITATIF - Diah Pradiatiningtyas; Chriswardana Bayu Dewa; Lina Ayu Safitri (LPPM Universitas Nusa Mandiri, 2025)
As a leading tourist destination, Yogyakarta has seen a significant increase in the number of visitors, which has also driven the use of digital platforms for accommodation needs. This study aims to analyze consumer satisfaction with the use of Online Travel Agent (OTA) applications for hotel reservations in Yogyakarta. The study employs a quantitative approach through a survey of 130 respondents who have made hotel reservations using OTAs such as Traveloka, Tiket.com, and Agoda. The data were analyzed using multiple linear regression with the aid of SPSS. The results indicate that the Price and Promotion variable has a significant influence on purchasing decisions, while other variables such as Service Quality, User Experience, and Security and Trust do not show significant partial effects. However, all variables collectively have a significant influence on purchasing decisions. These findings can serve as a reference for OTA application developers to enhance features related to pricing and cancellation policies in order to improve user satisfaction.